2014
DOI: 10.1371/journal.pone.0088331
|View full text |Cite
|
Sign up to set email alerts
|

Association of Bilateral Brachial-Ankle Pulse Wave Velocity Difference with Peripheral Vascular Disease and Left Ventricular Mass Index

Abstract: Unequal arterial stiffness had been associated with cardiovascular risks. We investigated whether an association existed between unequal arterial stiffness indicated by bilateral brachial-ankle pulse wave velocity (baPWV) difference and ankle-brachial index (ABI), baPWV, echocardiographic parameters and interarm and interankle systolic blood pressure (BP) differences. A total of 1111 patients referred for echocardiographic examination were included in this study. The BPs, ABI and baPWV were measured simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
1
13
0
1
Order By: Relevance
“…Previous studies showed that ABI <0.9 could be used for the prediction of stroke . Therefore, an interankle SBP difference of 7 mm Hg was compared with ABI <0.9.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that ABI <0.9 could be used for the prediction of stroke . Therefore, an interankle SBP difference of 7 mm Hg was compared with ABI <0.9.…”
Section: Resultsmentioning
confidence: 99%
“…Because lower limbs are more prone to be affected by PAD than upper limbs, IAND could be a better predictor of PAD than IAD [26]. High IAND was associated with increased left ventricular mass index [27] and arterial stiffness [28] and also predicted mortality in the elderly people [3]. Similarly, large ABID provided the prognostic value for mortality in patients undergoing chronic hemodialysis [5].…”
Section: Discussionmentioning
confidence: 99%
“…Hatsuda et al reported that arterial stiffness in different regions may affect CV disease differently, and that arterial stiffening did not occur uniformly in all arterial regions in patients with ischemic heart disease [103]. This imbalance in arterial stiffness has been associated with the risk of CV events, and an ABI < 0.9, high baPWV, and high LVMI have been independently associated with large differences in bilateral baPWV [104]. Furthermore, differences in bilateral baPWV have also been associated with an increased risk of CV and overall mortality in patients undergoing HD [105].…”
Section: Pwvmentioning
confidence: 99%